VP132 Cost Effectiveness Of A Predictive Risk Model In Primary Care. (12th January 2018) - Snooks, Helen; Porter, Alison; Evans, Bridie; Burge-Jones, Deborah; Davies, Jan; Hutchings, Hayley; Watkins, Alan; Whitman, Shirley; Sewell, Bernadette; Bailey-Jones, Kerry; Dale, Jeremy; Fitzsimmons, Deborah; et al.
Abstract : INTRODUCTION: Emergency admissions to hospital are a major financial burden on health services. In one area of the United Kingdom (UK), we evaluated a predictive risk stratification tool (PRISM) designed to support primary care practitioners to identify and manage patients at high risk of admission. We assessed the costs of implementing PRISM and its impact on health services costs. At the same time as the study, but independent of it, an incentive payment ('QOF') was introduced to encourage primary care practitioners to identify high risk patients and manage their care. METHODS: We conducted a randomized stepped wedge trial in thirty-two practices, with cluster-defined control and intervention phases, and participant-level anonymized linked outcomes. We analysed routine linked data on patient outcomes for 18 months (February 2013 – September 2014). We assigned standard unit costs in pound sterling to the resources utilized by each patient. Cost differences between the two study phases were used in conjunction with differences in the primary outcome (emergency admissions) to undertake a cost-effectiveness analysis. RESULTS: We included outcomes for 230, 099 registered patients. We estimated a PRISM implementation cost of GBP0.12 per patient per year. Costs of emergency department attendances, outpatient visits, emergency and elective admissions to hospital, and general practice activity were higher per patient per year in the intervention phase than control phase (adjusted δ = GBP76, 95 percent Confidence Interval, CI GBP46, GBP106), an effect that was consistent and generally increased with risk level. CONCLUSIONS: Despite low reported use of PRISM, it was associated with increased healthcare expenditure. This effect was unexpected and in the opposite direction to that intended. We cannot disentangle the effects of introducing the PRISM tool from those of imposing the QOF targets; however, since across the UK predictive risk stratification tools for emergency admissions have been introduced alongside incentives to focus on patients at risk, we believe that our findings are generalizable.